Personal Data Protection According to the Implemented Law in Indonesia and Japan - Ermania Widjajanti; Andi Widiatno Hummerson; Vience Ratna Multiwijaya; Dwi Alfianto (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The rapid development of technology creates various new things that can make human life easier, one of which is the cyber world which involves the internet. The presence of the cyber world brings many benefits to human life, with cyber, humans can do various things without being limited by distance and time. However, apart from bringing many positive things, the presence of the cyber world certainly creates new opportunities for crime, one of the threats in the cyber world is personal data. Indonesia and Japan, two countries that have significant economic and technological development in the Asian region, are not immune from the threat of personal data theft. Although both have different legal and cultural frameworks, both strive to protect the personal data of their citizens from increasingly complex cyber threats. In this way, a comparison will be made regarding the crime of personal data theft between Indonesia and Japan starting from the cultural history of respecting personal data in each country, the birth of regulations in each country, the criminal law system in each country, and also the regulations governing and has criminal sanctions in each country. The methodology used in this writing is a normative research. It is concluded that theft of personal data poses a significant challenge in the digital era, causing identity fraud, financial loss, and privacy violations. Indonesia and Japan, both Asian nations, have varying legal frameworks but both strive to protect citizens' data from cyber threats. Indonesia's regulations, passed in 2008, cover information and electronic transactions, intellectual property rights, and protection. Japan, on the other hand, has been addressing data protection since 2000, with regulations like APPI, My Number Act, and Act on Prohibition of Unauthorized Computer Access.